Whistleblower Protection as a Strategic Moderator: Enhancing Transparency and Reputation in Corporate Investment Decisions - Oktapriana, Chita; Ampri, Irfa (Asian Journal of Management Analytics, 2025)
Transparency and corporate reputation management are becoming increasingly important in today's investment decision-making process.  It looks at how Indonesian whistleblower protection laws affect investor decisions through Single Investor Identification (SID) and the relationship between transparency and company reputation.  The research study used a survey-based methodology to collect data from 415 local investors.  Research results demonstrated that corporate reputation and openness are powerful factors that favorably affect investors' decision-making. The study reveals how regulatory frameworks and corporate responsibility programs are crucial for fostering investor trust. The study gives politicians, businesses, and investors a basic grasp of how to improve market trust by implementing comprehensive whistleblower protection laws.